INISIATIF MASYARAKAT UNTUK MENGHINDARI BANK HARIAN: MENGGALI PERSEPSI NEGATIF MASYARAKAT - M. Khanif Ardzani; Fitriyani Jauharotun Nafisah (Islamic Banking Department, Faculty of Islamic Economics and Business, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, Indonesia., 2025)
This study examines the community's initiative to avoid everyday banks, focusing on the growing negative perceptions among individuals regarding the operational practices of these financial institutions. Although everyday banks offer easy access to loans, many perceive high interest rates and unclear terms as creating significant financial risks. Using a qualitative approach, this study explores the experiences and perspectives of those involved in the